IoT: Effective Authentication System (EAS) using Hash based Encryption on RFID Attacks - Dr. Janaki Sivakumar; Ms. Smitha Nayak; Dr. Amala Nirmal Doss (International Journal of Engineering and Management Research, 2020)
Internet of Things (IoT) is undoubtedly a well-known research area. Security on IoT communication services is the major challenge with advanced technology and devices. This paper mainly focusing on Perceptron layer based attacks and counter measures based on Effective Authentication System (EAS). This paper is ordered as outlining IoT Architecture, Types of Threats ,Perceptron Layer based attacks, sensor based communication services ,RFID mechanism ,Tag identify and verification by back end server and Hash based Effective Authentication System (EAS) to avoid pseudonym attacks .This paper proposes EAS as security measure by preventing privacy attack, pseudonym attack, location tracking and asynchronous attack.